Pursuing Paradigm Shift in Construction Safety Management: A Theoretical Introduction to the Safety Action Evaluation - Ahmed Jalil Al-Bayati; Keith J. Kowalkowski; Daniela Schröter (Advances in Civil Engineering)
Construction safety measurement metrics indirectly assess safety performance. Safety performance issues may be overlooked without a direct assessment technique, leading to occupational incidents and near misses being the only way to identify safety shortcomings. Managing occupational safety in this manner is unwise. This study proposed a new approach to integrate construction safety management into the responsibilities of frontline supervisors. Thus, the effectiveness of safety management efforts can be directly evaluated by monitoring the safety-related actions of frontline supervisors. A robust research methodology was employed to develop a first-of-its-kind safety performance evaluation system. By employing literature and the Delphi method, the research team identified 19 safety actions that could be undertaken by frontline supervisors to improve overall safety performance. Furthermore, two national surveys were used to assign a significant level to each action based on its impact and importance. Additionally, a rubric was created to objectively evaluate the implementation of the 19 identified actions. As a result, an evaluation system was developed to empower frontline supervisors to contribute to site safety. In addition, the presented framework would help improve overall construction safety management by swiftly addressing safety performance issues and safety effort deficiencies. The study provides a roadmap to directly assess safety performance by focusing on the safety-related actions of frontline supervisors. It significantly contributes to the body of knowledge by illustrating the possibility of integrating safety into the daily routines of project stakeholders and promoting collaboration among them. This represents a departure from traditional safety management techniques that primarily rely on safety personnel.